Social Learning Management System (Slms) For Technical Vocational Education And Training (Tvet) Program With Filtered Foul Words - et. al., Raquel SALAZAR (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to develop, deploy and evaluate a Social Learning Management System for the Technical Vocational Education Training (TVET) Programs with Filtered Foul Words as a tool for the faculty and students in the institution. Specifically, this sought to identify the challenges met and experienced by the respondents in conducting academic services and teaching-learning activities; levels of satisfaction on the features offered by the proposed system; and the issues encountered in the facilitation of the proposed system. After developing SLMS, researcher-made questionnaire was administered to the randomly selected 338 students and 14 faculty members from the Polytechnic University of the Philippines Institute of Technology to evaluate the proposed system. Rate and Weighted Mean were utilized in treating the information. The study reveals the challenges met and experienced by the respondents in conducting academic services and teaching learning activities. Aside from that, respondents are very satisfied in the usability, functionality, efficiency, reliability and portability features of the developed system. There were very minimal number of problems during the deployment of the system